The Functional Outcomes in Treatment of Displaced Extra Articular Distal Radius Fracture by Pop Alone or K-Wire Augmentation - Yasir Habib, Ali Shami, Muhammad Hanif, Obaid Ur Rahman, Muhammad Shehryar Zia, Wazir Ahmed, Ali Akhtar (Pakistan Journal of Medical & Health Sciences, 2022)
Background & Objective: A distal radius fracture is responsible for one-sixth visit to the orthopedic emergency room. Although these fractures are common, the best treatment for these fractures is still controversial. The objective of the study was to compare the functional outcomes in terms of union in displaced extra articular distal radius fracture by POP alone or k-wire augmentation. Methods: A comparative study was conducted in the department of orthopedic surgery, Pakistan Institute of Medical Science, Islamabad from June to December 2021. A total of sixty (n=60) adult patients irrespective of gender with distal radial fracture were included in the study. Patients allocated in two groups, Group A included patients who were treated with above elbow POP casting after reducing the fracture, under sedation or blockage of hematoma and Group B included the patients in whom surgery was performed with k-wire by closed reduction and internal fixation. The main outcome measure of the study was functional outcomes in terms of excellent, good and fair. The chi square test was used between study groups for comparison of acceptable outcomes (excellent to good). A p value ≤ 0.05 was considered significant. Results: The average age of the patients of both groups was 38.6±15.8 years. Among 60 patients, 70% (n=42) were male and 30% (n=18) were females. In group A (POP) 30% (n=9) patients showed excellent, 23.3% (n=7) showed good and 46.7% (n=14) showed fair outcome as per our study outcomes. In group B (k-wire) 56.7% (n=17) patients showed excellent, 36.7% (n=11) showed good and 6.6% (n=2) showed fair outcome with p value 0.002. Conclusions: The study concluded that the functional outcomes in terms of union of displaced extra articular distal radius fractures, K-wire fixation showed better results than POP cast alone. Keywords: Bone wires; Casts, Surgical; Internal fixators; Radius fractures.